The effectiveness of a mouth guard to protect against strong occlusion caused by modified electroconvulsive therapy. Issue 5 (19th February 2014) - Ogami, Saori; Yamada, Morimasa; Kanazawa, Mayuko; Takeda, Kiyoshi; Kimura, Naoaki; Mizutani, Hideki; Kohase, Hikaru; Fukayama, Haruhisa
Abstract Modified electroconvulsive therapy (m‐ECT) is a treatment for mental disease such as depressive disorder. Although a muscle relaxant is used during current application, strong occlusion occurs due to the proximity of the electrode to the temporal and masseter muscles. Although a feedback mechanism to avoid excessive occlusion occurs unconsciously, the mechanism does not work under general anesthesia. Strong occlusion may cause complications such as tooth injury, pain of the jaw, lip laceration, and bleeding of the gums. Although there was a report that the insertion of shock‐absorbing materials such as gauze reduces complications, there has been no study on the effectiveness of a mouth guard (MG) for alleviating the occlusal force during m‐ECT. The present study investigated the effectiveness of MG for alleviation of the occlusal force and complications during m‐ECT. An ethyl‐vinyl‐acetate (EVA) MG was used as a shock‐absorbing material to mitigate the strong occlusion during m‐ECT to investigate the influence of MG on the occlusal force and its effectiveness. The results showed that the occlusal force was alleviated by 58 ± 22% on average using MG during m‐ECT. It also helped reduce intra‐oral problems such as pain and bleeding. The results suggest the effectiveness of MG for alleviating the occlusal force during m‐ECT and avoiding complications due to strong occlusion.